Transformation in South African professional nursing organisations: The strive for unity - Esterhuizen, Johanna M.; Van Rensburg, Gisela H. (Contree, 2024)
South Africa’s professional nursing organisations and consequently the profession itself, underwent two major periods of transformation. The first period from the 1950s to the 1980s, was shaped by a political system that forbade multiracial workers’ organisations and mandated racially segregated nursing associations. The statutory position of the South African Nursing Association (SANA), combined with the country’s autocratic socio-political environment, limited the ability of nurse leaders to openly challenge the status quo. Instead, these leaders developed strategies and professional structures to minimise the impact of socio-political influences on the development of nursing as a profession. The second period of transformation began in the 1980s, driven by broader socio-political changes in South Africa. The racial fragmentation caused by the first transformational period, coupled with SANA’s statutory status, made this second period particularly challenging. Over time the nursing profession experienced further division because of differing philosophical and socio-political views. From 1944 to 1985, nurse leaders opted for a single, mandatory professional association to represent professional nurses’ interests. However, after 1985, professional nurses in South Africa chose to prioritise freedom of association and their socio-economic needs, which led to the erosion of a unified, collective professional identity.Contribution: The authors contribute to the history of nursing by describing how South African professional nursing organisations were subjected to two transitional periods that significantly influenced the nature of the organisations and the nursing profession itself. The purpose of this article is to narrate these events not yet disseminated in South African nursing history literature.